Technologie informacyjne w świetle praktyk czytelniczych - Kęsy, Marek (Wydawnictwo Uniwersytetu Rzeszowskiego, 2018)
Rozwój techniczny wywołuje zmiany warunków życia współczesnego człowieka powodując przemiany osobowościowe, wzorce kulturowe, sposób postrzegania siebie i innych. Przykładem przeobrażeń społecznych są przemiany w praktykach czytelniczych, w których tradycyjne formy przekazu informacji i wiedzy zastępowane zostają formami przekazu elektronicznego.

Technological development causes changes in the living conditions of contemporary people, resulting in personality changes, cultural patterns and the way people perceive themselves and others. An example of social transformation are changes in reading practices, in which traditional forms of information and knowledge transfer are replaced by forms of electronic communication.
Information technologies in the light of reading practices
Keywords: technologia informacyjna; Internet; czytelnictwo; praktyki czytelnicze; information technology; reading; reading practices